2010
DOI: 10.1111/j.1469-7610.2009.02199.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of callous and unemotional traits in the diagnosis of conduct disorder

Abstract: Subtyping CD using CU traits identifies children with more severe and persistent psychopathology. Children with high CU traits but no CD diagnosis require further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
168
2
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(184 citation statements)
references
References 35 publications
12
168
2
2
Order By: Relevance
“…These data are consistent with previous studies linking higher CU traits to earlier onset of antisocial activity and to earlier contacts with the police and other authorities (e.g., Dadds et al, 2005;Loeber et al, 2005;Pechorro et al, 2014), and reinforce the role of the interrelationship of CU traits with early criminal onset (e.g., Dandreaux & Frick, 2009;Rowe et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These data are consistent with previous studies linking higher CU traits to earlier onset of antisocial activity and to earlier contacts with the police and other authorities (e.g., Dadds et al, 2005;Loeber et al, 2005;Pechorro et al, 2014), and reinforce the role of the interrelationship of CU traits with early criminal onset (e.g., Dandreaux & Frick, 2009;Rowe et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…With regard to the correlations of the CD LPE specifier with age of crime onset and age of first problem with the law we found they were statistically significant for both genders, reinforcing the role of the interrelationship of CU traits with early criminal onset (e.g., Dandreaux & Frick, 2009;Rowe et al, 2010). Significant correlations were also found with other variables (e.g., crime seriousness), at least regarding the male participants.…”
Section: Discussionsupporting
confidence: 65%
“…Significant differences were found regarding the criminal variables: results showed that the participants from the High CU traits group had an earlier age of crime onset and were younger when they had their first problem with the law, but only marginally significant differences were found in terms of age of first detention. These data are consistent with previous studies linking higher CU traits to earlier onset of antisocial activity and to earlier contacts with the police and other authorities (e.g., Dadds et al, 2005;Loeber et al, 2005), and reinforce the role of the interrelationship of CU traits with early criminal onset (e.g., Dandreaux & Frick, 2009;Rowe et al, 2010). We also found that the High CU traits group had a higher proportion of youths diagnosed with Conduct Disorder (APA, 2013), and the very high prevalence rate of conduct disorder we found in our total sample (91.3%) was in the higher range of what is typical of some forensic samples (Sevecke & Kosson, 2010).…”
Section: Discussionsupporting
confidence: 82%
“…While we acknowledge that some researchers view antisocial behavior as an integral part of psychopathy (e.g., Hare & Neumann, 2005), many theoretical models view it as a secondary characteristic that develops as a result of the core personality features (e.g., Skeem & Cooke, 2010). Furthermore, recent research supports the existence of CU traits in the absence of conduct problems and finds them to be significantly related to adjustment problems in youth without significant conduct problems (Kumsta, Sonuga-Barke & Rutter, 2011;Rowe et al, 2010).…”
Section: Present Studymentioning
confidence: 99%